Evolutionary characteristics of export trade network in the Arctic region - Xing Ma; Wenli Qiang; Shijin Wang; Jiayi Liu; Arunima Malik; Mengyu Li; Xiang Wang (Regional Sustainability)
The economic potential induced by environmental changes in the Arctic region garnered substantial interest, which positions Arctic trade as a crucial indicator in forecasting the impacts of climate change on the global economy. Nevertheless, attention devoted to the evolving dynamics of trade in the Arctic region remains scarce. In this study, we constructed export trade network in the Arctic region (including Denmark, Finland, Sweden, Norway, Iceland, the Canadian Arctic, the Russian Arctic, Alaska State of the USA, and Greenland) from 1990 to 2019 and analyzed its topology and evolutionary characteristics through complex network theory. We used a structural entropy index based on the distribution of the number of trading partners and the degree of trade concentration to assess export diversity, while we also utilized a revealed comparative advantage index to evaluate product export competitiveness using the share of trade volume of each type of product. The results indicate that the total export trade in the Arctic region increased by 53.4% during 1990–2019, with the most significant growth observed in the exports of chemical products and mineral fuels. The increasing complexity of trade network in the Arctic region resulted in the region’s export destinations no longer being concentrated on a few major countries and regions. The proportion of exports from the Arctic region to Europe decreased by 13.5%, while the proportion of exports from the Arctic region to Asia and North America increased by 6.8% and 3.1%, respectively. The Arctic region exhibited clear distinctions in the range of flows of different products, and its export trade was becoming increasingly diversified. Although differences in comparative advantages between products within individual countries or regions have narrowed, substantial gaps persist. The findings of this study can enhance the comprehensive understanding of the significance and function of Arctic trade activities within the global economy, providing a scientific basis for addressing the associated challenges and opportunities in the context of climate change.